Development of a patient-reported outcome measure (PROM) and change measure for use in early recovery following hip or knee replacement - Louise H. Strickland; David W. Murray; Hemant G. Pandit; Crispin Jenkinson (SpringerOpen, 2020)
Abstract Background Hip and knee replacement are effective procedures for end-stage arthritis that has not responded to medical management. However, until now, there have been no validated, patient-reported tools to measure early recovery in this growing patient population. The process of development and psychometric evaluation of the Oxford Arthroplasty Early Recovery Score (OARS), a 14-item patient-reported outcome measure (PROM) measuring health status, and the Oxford Arthroplasty Early Change Score (OACS) a 14-item measure to assess change during the first 6 weeks following surgery is reported. Patients and methods A five-phased, best practice, iterative approach was used. From a literature based starting point, qualitative interviews with orthopaedic healthcare professionals, were then performed ascertaining if and how clinicians would use such a PROM and change measure. Analysis of in-depth patient-interviews in phase one identified important patient-reported factors in early recovery which were used to provide questionnaire themes. In Phase two, candidate items from Phase One interviews were generated and pilot questionnaires developed and tested. Exploratory factor analysis with item reduction and final testing of the questionnaires was performed in phase three. Phase Four involved validation testing. Results Qualitative interviews (n = 22) with orthopaedic healthcare professionals, helped determine views of potential users, and guide structure. In Phase One, factors from patient interviews (n = 30) were used to find questionnaire themes and generate items. Pilot questionnaires were developed and tested in Phase Two. Items were refined in the context of cognitive debrief interviews (n = 34) for potential inclusion in the final tools. Final testing of questionnaire properties with item reduction (n = 168) was carried out in phase three. Validation of the OARS and OACS was performed in phase four. Both measures were administered to consecutive patients (n = 155) in an independent cohort. Validity and reliability were assessed. Psychometric testing showed positive results, in terms of internal consistency and sensitivity to change, content validity and relevance to patients and clinicians. In addition, these measures have been found to be acceptable to patients throughout early recovery with validation across the 6 week period. Conclusions These brief, easy-to-use tools could be of great use in assessing recovery pathways and interventions in arthroplasty surgery.